ANALISIS PENGARUH STRUKTUR MODAL, KEBIJAKAN DIVIDEN, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN: STUDI PADA PERUSAHAAN LQ45 NON KEUANGAN PERIODE 2020-2022 - Fardiana, Fardiana; Istiono, Istiono (Cahaya Ilmu Bangsa, 2024)
Intense business competition forces companies to demonstrate their best performance to attract investors and facilitate the acquisition of funds through the capital market. The Indonesia Stock Exchange (IDX) plays a crucial role in helping companies sell shares to investors, which in turn provides additional capital for the companies. Companies listed in the LQ45 index also face strategic decisions regarding capital structure, dividend policy, and profitability to maintain their company value. This study aims to analyze the influence of capital structure, dividend policy, and profitability on the value of non-financial LQ45 companies during the 2020-2022 period. Based on data analysis, it was found that capital structure significantly impact company value, while dividend policy and profitability does not have a significant effect. However, simultaneously, these three variables significantly influence company value. This research provides insights for management and shareholders in planning financial and business strategies to enhance company value in the future.